Effect of physical activity on fasting blood glucose and lipid profile among low income housewives in the MyBFF@home study - Azahadi Omar; Mohd Normazlan Husain; Ahmad Taufik Jamil; Noor Safiza Mohamad Nor; Rashidah Ambak; Mansor Fazliana; Nur Liyana Ahamad Zamri; Tahir Aris (BMC, 2018)
Abstract Background Regular physical activity has always been strongly recommended for good cardiovascular health. This study aimed to determine the effect of physical activity on fasting blood glucose and lipid profile among low income housewives in Klang Valley. Methods Data of 328 eligible housewives who participated in the MyBFF@Home study was used. Intervention group of 169 subjects were provided with an intervention package which includes physical activity (brisk walking, dumbbell exercise, physical activity diary, group exercise) and 159 subjects in control group received various health seminars. Physical activity level was assessed using short-International Physical Activity Questionnaire. The physical activity level was then re-categorized into 4 categories (active intervention, inactive intervention, active control and inactive control). Physical activity, blood glucose and lipid profile were measured at baseline, 3rd month and 6th month of the study. General Linear Model was used to determine the effect of physical activity on glucose and lipid profile. Results At the 6th month, there were 99 subjects in the intervention and 79 control group who had complete data for physical activity. There was no difference on the effect of physical activity on the glucose level and lipid profile except for the Triglycerides level. Both intervention and control groups showed reduction of physical activity level over time. Conclusion The effect of physical activity on blood glucose and lipid profile could not be demonstrated possibly due to physical activity in both intervention and control groups showed decreasing trend over time.